Specific features of single-pulse femtosecond laser micron and submicron ablation of a thin silver film coated with a micron-thick photoresist layer. (31st May 2015) - Zayarnyi, D A; Ionin, A A; Kudryashov, S I; Makarov, S V; Rudenko, A A; Drozdova, E A; Odinokov, S B
Abstract Specific features of ablation of a thin silver film with a 1-μm-thick layer of a highly transparent photoresist and the same film without a photoresist layer under single tightly focused femtosecond laser pulses in the visible range (515 nm) are experimentally investigated. Interference effects of internal modification of the photoresist layer, its spallation ablation from the film surface and formation of through hollow submicron channels in the resist without its spallation but with ablation of the silver film lying under the resist are found and discussed.